2020
DOI: 10.1002/jmv.26103
|View full text |Cite
|
Sign up to set email alerts
|

Clearance and persistence of SARS‐CoV‐2 RNA in patients with COVID‐19

Abstract: Patients with coronavirus disease‐2019 may be discharged based on clinical resolution of symptoms, and evidence for viral RNA clearance from the upper respiratory tract. Understanding the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) viral clearance profile is crucial to establish a re‐testing plan on discharge and ending isolation of patients. We aimed to evaluate the number of days that a patient needed to achieve undetectable levels of SARS‐CoV‐2 in upper respiratory tract specimens (nasophar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
81
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 18 publications
12
81
1
7
Order By: Relevance
“…Despite the observation that some COVID-19 patients initially test negative by real-time PCR (1, 2), a dichotomous observation has been the persistent detection of SARS-CoV-2 RNA in other patients (7). A number of published reports have demonstrated that SARS-CoV-2 real-time PCR assays may be positive for weeks, even following the resolution of clinical symptoms (7,8). The author is aware of a case where a patient with an underlying health condition tested positive by PCR for over 100 days (unpublished data).…”
Section: The Clinical Sensitivity Of Pcr and Its Use As A Test-of-curementioning
confidence: 99%
“…Despite the observation that some COVID-19 patients initially test negative by real-time PCR (1, 2), a dichotomous observation has been the persistent detection of SARS-CoV-2 RNA in other patients (7). A number of published reports have demonstrated that SARS-CoV-2 real-time PCR assays may be positive for weeks, even following the resolution of clinical symptoms (7,8). The author is aware of a case where a patient with an underlying health condition tested positive by PCR for over 100 days (unpublished data).…”
Section: The Clinical Sensitivity Of Pcr and Its Use As A Test-of-curementioning
confidence: 99%
“…Preliminary results from the RECOVERY trial showed that low-dose dexamethasone reduced deaths by one-third; however, the results were restricted to patients who needed ventilation [21,28]. Clinical outcomes are the most important endpoints; however, the duration of RNA clearance was used as an observational indicator in previous studies [14,29,30]. Studies on MERS showed that corticosteroid therapy was associated with delayed RNA clearance [14].…”
Section: Discussionmentioning
confidence: 99%
“…Although there have not been any confirmed cases, blood banks should implement screening for possible SARS-CoV-2 contamination to ensure the safety of blood and blood products in the present COVID-19 pandemic situation. Nevertheless, viral particles can be detected in convalescent patients for a long time [9]. This is an important issue since interest has emerged in using donated convalescent plasma from patients recovering from COVID-19 to treat COVID-19 patients [10].…”
Section: Blood-borne Transmissionmentioning
confidence: 99%